Integration of Digital Ethics into Islamic Religious Education: A Case Study at Vocational High School - Eri Murniasih; Wasehudin Wasehudin; Siti Patimah; Rizki Pebrina (Ta'dib, 2025)
The development of digital technology has brought significant changes to student behavior patterns, ways of thinking, and value systems, particularly at the vocational secondary education level. While digital technology opens up significant opportunities for improving the quality of learning, it also raises various ethical issues. This situation demands the integration of digital ethics into the educational process, including in Islamic Religious Education (PAI), which has a strategic mandate in shaping students' character and morals. This study aims to describe how the integration of digital ethics is implemented in Islamic Religious Education (PAI) learning at Vocational High School 4, Serang City (SMKN 4 Serang), as well as to identify the roles of teachers, curriculum, and school culture in supporting the internalization of Islamic-based digital ethical values. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation studies. Research informants included two Islamic Religious Education (PAI) teachers, the vice principal for curriculum, and 24 students. The results show that the integration of digital ethics in PAI is carried out through a process of transinformation in the form of strengthening Islamic moral values, then value transactions in the contextualization of teaching materials with digital phenomena, teacher role models, and transinternalization in the form of habituation of ethical digital behavior in the school environment. These findings emphasize the strategic role of PAI in shaping students' digital ethical awareness, despite still being hampered by teachers' digital competence and suboptimal school policies.